Pengembangan Niat Adopsi Mobile Wallet: Integrasi Model UTAUT2 dengan Social Connectedness dan Culture - Felick Kurnia (Jurnal Rekayasa Sistem Industri, 2021)
Smartphone technology is rising rapidly around the world. It allows various companies including financial institution to improve services for their customers. Mobile wallet is a cashless payment system that is carried out with a mobile phone. Since 2010, The Central Bank of Indonesia has been encouraging the adoption of cashless payment system, including mobile wallet. Despite the efforts made, the use of cashless payment system in Indonesia is still low. This paper investigates the determinants of customers’ intention to adopt mobile wallet using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) Model. It offers theoretical contributions by extending UTAUT2 with social connectedness and culture. Empirical data from 139 Indonesian customers were used to test the proposed model using partial least square structural equation modeling. It was found that performance expectancy, hedonic motivation, price value, and habits significantly influence customers’ intention to adopt mobile wallet. This study also found that social connectedness significantly affects performance expectancy and effort expectancy. The findings of this study would also be beneficial for mobile wallet providers to develop effective strategies to increase the use of mobile wallet in Indonesia.